Enhancing Nutritional Quality of Unleavened Wheat Flatbread Using Oyster Mushroom flour: Elevating Wheat Flatbread's Nutritional Profile with Mushroom Flour - Dhillon, Gurpreet Kaur; Mahajan, Monika (Mushroom Research, 2023)
Whole wheat meal was supplemented with oyster mushroom flour (OMF) to create a healthier versionof unleavened flatbread. Oyster mushrooms were sundried and ground into flour to supplement at 5,10, 15 and 20% in whole wheat meal. The addition of OMF significantly increased the water absorption(%) of dough, while dough handling was smooth and non-sticky. Prepared flatbreads showed fullpuffing in control, 5, 10 and 15% inclusion levels, while partial puffing was observed in flatbreadcontaining 20% OMF. OMF significantly improved the flatbread’s crude protein, crude fibre, andash content. Moreover, compared to the control, a significant increase was observed in the in vitroprotein digestibility (IVPD) of supplemented flatbreads. The sensory evaluation suggested that up to15% OMF level in flatbread did not alter the sensory attributes and was acceptable and comparablewith the wheat flatbread. Further, the trainees appreciated the dissemination of the technology usingthe household processing technique as it provides an economical means to add mushroom protein ofhigh biological value to staple food.